Digitalisasi UMKM Z-Chicken Baznas Kota Tangerang melalui GoFood, QRIS, dan Google Maps - Muhammad Fathi Taqiyuddin; Anisya Septiawati Purnomo; Lisna Damayanti; Najmah Zaahirah; Fatimah Zahro Fadilah; Evan Azalia Ibnu Arianto; Asep Usman Ismail (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The advancement of digital technology compels business owners to adapt to various digital platforms to enhance competitiveness and expand market reach. This community service initiative targets Z-Chicken outlet operators supported by the National Zakat Agency (BAZNAS) of Tangerang City, who face challenges in utilizing digital technology—such as the lack of digital payment systems, failure to register as food delivery merchants, and the absence of business locations on digital mapping platforms. The project aims to support the digital transformation of these businesses through the implementation of QRIS, GoFood Merchant services, and Google Maps, thereby improving accessibility, transaction efficiency, and marketing reach. Conducted between April and May 2026, the initiative employed a participatory mentoring method comprising partner needs assessment, outreach and education, and implementation support. A comparative descriptive analysis was used to evaluate the partners' conditions before and after the mentoring process based on specific performance indicators. The results indicate that all 14 participating outlets successfully secured active QRIS accounts and registered on Google Maps, while 13 outlets successfully registered as GoFood merchants. The implementation of digitalization led to increased business visibility, expanded marketing access, streamlined transactions, and improved discoverability for consumers. Participatory mentoring proved effective in enhancing the capacity of business owners to adopt digital technologies, thereby supporting the sustainability of their culinary businesses.